Database Sumberdaya Lahan Pertanian Pangan Berkelanjutan Berbasis Remote Sensing dan Sistem Informasi Geografis di Subak Temaga Kecamatan Denpasar Timur - ARDHIA AYU PRADITHA; INDAYATI LANYA; MADE SRI SUMARNIASIH (Fakultas Pertanian Universitas Udayana, 2021)
Database of Sustainable Food Agricultural Land Resources Based on Remote Sensing and Geographical Information System at Subak Temaga East Denpasar Subdistricts. Subak Temaga doesn’t yet have a database according to Government Regulation No. 25 of 2012 concerning Information System for Sustainable Food Agriculture Land (SFAL). A geospatial-based database needs to be compiled to implement these regulation. The research aims: compile a database of artificial resources, agricultural resources, land resources and human resources to support SFAL in Subak Temaga, create land ownership maps in Subak Temaga, compile an information system of SFAL and land ownership based on remote sensing and Geographic Information System (GIS). This research uses a survey method to obtain primary data, then doing the mapping to compile the information system based on geospatial. The research results: artificial resources (irrigation, jogging track/farm road), land resources (soil family, landform, slope, rainfall, land suitability, soil fertility), agricultural resources (types of farm commodities, productivity, agriculture tools and machinery, cropping pattern, types and dosage of fertilizer), human resources (name, address, age, last education, farmer status, ownership status, ownership large and boundary, profit-sharing system). Farmer status consists of 56 owner farmers (30,9%) and 125 sharecropers (69,1%). Land ownership status consist of 432 freehold polygons (92,7%) and 34 non freehold polygons (23.8%). Remote sensing is used to determine the boundaries of land ownership, GIS is used to compile a geospatial-based information system for LP2B and land ownership.